NMR spectroscopy in food analysis - Spyros, Apostolos Dais, Photis (RSC Publishing, 2013)
"Current developments in the field covered in this book are the availability of solid state NMR experiments such as CP/MAS and more importantly HR-MAS NMR for the analysis of semisolid foods, and the increasing use of chemometrics to analyze NMR data in food metabonomics. Moreover, this book contains an up to date discussion of MRI in food analysis including topics such as food processing and natural changes in food such as ripening."--Publisher.